Collaborative Networks for Effective Ecosystem‐Based Management: A Set of Working Hypotheses. Issue 2 (18th January 2016) - Bodin, Örjan; Sandström, Annica; Crona, Beatrice
Abstract : Ecosystem‐based management (EBM) represents a comprehensive approach to better govern the environment that also illustrates the collaborative trend in policy and public administration. The need for stakeholder involvement and collaboration is strongly articulated, yet how and for what purposes collaboration would be effective remains largely untested. We address this gap by developing and evaluating a set of hypotheses specifying how certain patterns of collaborations among actors affect their joint ability to accomplish EBM. Content analyses of management plans drawn from five EBM planning processes in Sweden are combined with analyses of the collaborative networks through which these plans have been developed. Our results indicate that system thinking and the ability to integrate across different management phases are favored by collaborations between different kinds of actors, and by project leaders being centrally located in the networks. We also find that dense substructures of collaboration increase the level of specificity in the plans in regards to explicating constraints on human activities. Having many collaborative ties does however not enhance the overall level of specificity. Our results also show that different network characteristics can give rise to similar EBM outcomes. This observed equifinality suggests there is no single blueprint for well‐performing collaborative networks.